Human papillomavirus and male infertility correlation analysis following World Health Organization 2021 guidelines - Tiziana Notari; Michela Buttà; Nicola Serra; Arianna Sucato; Giovanni Rizzo; Giuseppina Capra; Liana Bosco (Scientific Reports)
Abstract Male infertility is a complex issue influenced by multiple environmental and pathological factors. In this context, the impact of Human papillomavirus (HPV) infection on male fertility remains controversial. The introduction of new WHO 2021 evaluation criteria, included in the 6th ed. of Laboratory Manual for the examination and processing of human semen, i.e. DNA fragmentation index (DFI), slow and rapid progressive motility, could provide additional information about this correlation. 121 semen samples of male partners of HPV-positive women attending In Vitro Fertilization (IVF) were evaluated following WHO 2021 and HPV-DNA test. Comparing HPV-negative and positive samples for rapid and slow progressive motility showed significantly different results (p = 0.0018, p = 0.0004), contrary to what was observed for total progressive motility. Regarding sperm DFI, only high-risk HPV infections affected DNA integrity. In addition, the correlation between the different semen parameters revealed a significant correlation between midpiece morphological defects and rapid progressive motility in the HPV-positive group (rho = 0.43, p = 0.0006). In conclusion, WHO 2021 provides additional information regarding HPV’s impact on seminal parameters. The correlation between HPV positivity, midpiece defects and a higher rapid progressive motility opens new research perspectives that may help unravel the issues surrounding the role of HPV in compromising sperm quality.